Tanggung Jawab Perusahaan atas Ketersediaan Alat Pelindung Diri bagi Tenaga Kerja di Pabrik Kaleng Berdasarkan Permenaker No. 8 Tahun 2010 Perspektif Maqāṣid Al-Syarī‘Ah - Panggabean, Fahmi Arrahman; Zahara, Fatimah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze corporate responsibility in providing Personal Protective Equipment (PPE) for workers at the can manufacturing factory of CV. Murni Sarkum based on the Regulation of the Minister of Manpower of the Republic of Indonesia No. 8 of 2010 from the perspective of maqāṣid al-sharīʿah. The research employs a qualitative approach with an empirical juridical method, examining the relationship between applicable legal norms and their implementation in practice. Primary data were obtained through interviews and direct observation of workplace safety policies, while secondary data were derived from statutory regulations—particularly Ministerial Regulation No. 8 of 2010 concerning Personal Protective Equipment and Law No. 13 of 2003 on Manpower—as well as scholarly literature on maqāṣid al-sharīʿah and Islamic business ethics. The findings indicate that the provisions of Ministerial Regulation No. 8 of 2010 are substantively aligned with the principles of maqāṣid al-sharīʿah, especially ḥifẓ al-nafs (protection of life), which emphasizes the importance of occupational safety and health. However, its implementation in the factory remains suboptimal, as the provision of PPE tends to be carried out merely as an administrative obligation and is not accompanied by adequate supervision, training, and worker awareness. This study concludes that the maqāṣid al-sharīʿah approach can serve as an ethical paradigm in occupational safety and health practices, where the provision of PPE is understood not only as a legal obligation but also as a moral and social responsibility aimed at safeguarding human life and promoting public welfare.